“NADIE SABE PARA QUIÉN TRABAJA”. LA IDENTIFICACIÓN DEL EMPLEADOR (O DE LOS EMPLEADORES) EN LOS GRUPOS DE EMPRESAS EN EL PERÚ. - Ubillús Bracamonte, Rolando Enrique (2019)
Business —and especially corporate— grouping is a subject of great topicality and never ceases to be studied and discussed in the literature and social jurisprudence from around the globe. A review of the jurisprudence repertoires clearly shows an exponential increase of the number of judgements passed on the subject, but at the same time the difficult character of many issues arising thereof.Because of these circumstances, this paper doesn’t intend to provide a comprehensive overview of Peruvian Law on corporate groups, a task that would be impossible in the affordable space; nor do we want to submit a definitive regulation proposal tackling all the problems generated by this form of business organization. Instead, we are trying to provide guidelines for the identification of the person or persons acting as employers inside a corporate group.